Prevalence of Entamoeba histolytica and other enteral parasitic diseases in the metropolitan region of Belo Horizonte, Brazil. A cross-sectional study - Costa, Juliana de Oliveira; Resende, José Adão; Gil, Frederico Ferreira; Santos, Joseph Fabiano Guimarães; Gomes, Maria Aparecida (São Paulo Medical Journal, 2018)
BACKGROUND: Enteral parasitic diseases are a public health problem in nations with low economic development and in settings with poor sanitation. Amebiasis is the second most frequent form of parasitosis, with a high burden of disease. Knowledge of the prevalence of enteroparasitoses in a given region is useful for planning clinical decision-making. Thus, the aim of this study was to estimate the prevalence of enteral parasitic diseases, especially amebiasis, through analysis on stool samples from public and private laboratories in a metropolitan area in southeastern Brazil. DESIGN AND SETTING: Cross-sectional study conducted in the metropolitan region of Belo Horizonte, Brazil. METHODS: We evaluated 6,289 fecal samples from one private and one public laboratory. The samples were concentrated by means of spontaneous sedimentation, and those that were positive for Entamoeba histolytica or Entamoeba dispar in optical microscopy analyses were processed to obtain deoxyribonucleic acid, with subsequent identification through the polymerase chain reaction. RESULTS: Among the stool samples, 942 (15.0%) had parasitic infections; 73 (1.2%) of these were helminthic infections and 847 (13.5%) were protozoan infections, caused mainly by Escherichia coli (6.0%), Endolimax nana (5.2%) and Giardia lamblia (1.2%). Infections due to Entamoeba histolytica or Entamoeba dispar occurred in 36 samples (0.6%) and the polymerase chain reaction revealed five (13.9%) as Entamoeba histolytica. CONCLUSION: The prevalence of enteral parasitic diseases is high in the metropolitan region of Belo Horizonte, although amebiasis may not be a problem.